Physical growth of students aged 10 to 14 on Santa Catarina island Crescimento físico de escolares da ilha de Santa Catarina - Machado Z.* (2001)
The purpose of this study was to verify, by means of socioeconomic and cultural indicators, the profile of development and physical growth of students aged from 10 to 14, both native and non-native to Florianópolis, Santa Catarina Island, state of Santa Catarina, Brazil, and to investigate whether natives differ from nonnatives. The casual comparative method (Gay, 1987) was employed and supplemented with the person-context paradigm (Bronfenbrenner, 1991). The study enrolled 365 students of both sexes: 265 of them natives and 100 non-natives. Physical growth was assessed in terms of body weight and height, with the NCHS curves as reference standard. Data were analyzed by means of descriptive statistics, the chi-square test, Student's t test of Student and Pearson's correlation coefficient. The results show that locals have greater body weight than non-locals and that both groups exhibit lower weight than the NCHS standard values. Values for height were also greatest on the NCHS scale, followed by natives and then non-natives. It was observed that the macrosystem of Santa Catarina Island, analyzed in the light of socio-economic and cultural indicators, is homogeneous for the students that were analyzed here and is therefore able to have the same influence on their development profiles. We may add that this influence on the students is positive.